Antropocæne fortællinger: Mindre end én, flere end mange - Ejsing, Mads (K&K - Kultur og Klasse, 2020)
This article discusses three different theoretical narratives about the anthropocene that have gained significant traction within the social science literature in recent years: the Ecomodernist, the eco-Marxist and the New Materialist. In an attempt to move beyond the abstract character of much of the debate around the anthropocene, the article brings these three theoretical narratives into conversation with ethnographic field work carried out in a small rural community on the West Coast of Denmark. By juxtaposing the theoretical narratives with a series of small local stories, through what the anthropologist Anna Tsing has called “a rush of stories,” the article seeks to make two interventions into the debates about the anthropocene. First, it argues that the conceptual openness of the anthropocene, which has led to neologisms such as the capitalocene, the chthulucene and the plantationocene, is in fact part of its strength, not its weakness. As the stories from the field illustrate, the different realities that the three theoretical narratives point to are in fact able to exist alongside each other. Secondly, and due in part to this conceptual openness, the article argues for supplementing the abstract theoretical discussions of the anthropocene with more situated approaches that study how the anthropocene unfolds in a specific time and place. The world of the anthropocene is a myriad of different, local, interrelated and overlapping realities. Relying on a single global narrative about the anthropocene neglects that multiplicity.